Analisis Prospek Kawasan Ekonomi Khusus (KEK) Bitung - Lihiang, Elisabeth Agustina (JURNAL RISET BISNIS DAN MANAJEMEN, 2016)
KEK Bitung will provide many benefits for both economic developments for the North Sulawesi province, Eastern Indonesia, the Republic of Indonesia and even the World(especially Asia Pacific). KEK Bitung proposed by commodity based on the superiority of North Sulawesi Province, which is Coconut / derivative products, fishery / derivatives productand added with products that have great potential in the future, i.e. logistics. The results showed that for the financial feasibility analysis then found Bitung KEK in a financially suitable to do. For the public perception is essentially KEK Bitung considered to provide benefits or positive impacts to the surrounding community. The common factors are 1). social aspects of society, 2) Business opportunities, 3). Entrepreneurship, 4). The price of land 5). PAD (revenue) and Agricultural product prices, 6) the ability to socialize and fishery product prices 7). Bitung City landmarks. For the perception of potential investors or tenants all states interested in joining the KEK Bitung. To support the critical infrastructure in the KEK Bitung has the potential to be developed and able to fulfill the needs in KEK Bitung.Keywords: KEK Bitung, Financial Feasibility, communities, investors, Infrastructure